2014
DOI: 10.1098/rspb.2013.3221
|View full text |Cite
|
Sign up to set email alerts
|

On signals of phase transitions in salmon population dynamics

Abstract: Critical slowing down (CSD) reflects the decline in resilience of equilibria near a bifurcation and may reveal early warning signals (EWS) of ecological phase transitions. We studied CSD in the recruitment dynamics of 120 stocks of three Pacific salmon (Oncorhynchus spp.) species in relation to critical transitions in fishery models. Pink salmon (Oncorhynchus gorbuscha) exhibited increased variability and autocorrelation in populations that had a growth parameter, r, close to zero, consistent with EWS of extin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…For example, we found strong fluctuations in nonlinearity estimates, especially in the exploitation scenario (electronic supplementary material, figure S2f). Changes in variance and autocorrelation can also be unreliable in the presence of short time series [51], high levels of stochasticity [57], fast changing stress drivers [54,58] or due to portfolio effects [56] and life-history strategies [59]. Further research is needed to find if similar constraints hold for the elevated nonlinearity indicator we propose here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we found strong fluctuations in nonlinearity estimates, especially in the exploitation scenario (electronic supplementary material, figure S2f). Changes in variance and autocorrelation can also be unreliable in the presence of short time series [51], high levels of stochasticity [57], fast changing stress drivers [54,58] or due to portfolio effects [56] and life-history strategies [59]. Further research is needed to find if similar constraints hold for the elevated nonlinearity indicator we propose here.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that an ecosystem manager could estimate both CSD and EDM metrics in order to rank populations according to their stability [55]. For instance, Krkosek & Drake [56] looked at patterns of CV and AR1 for Pacific salmon populations and found that they were higher for pink salmon stocks that had a population growth rate close to zero. In this work, the authors assumed that salmon populations would suffer a transcritical bifurcation due to growth rates approaching zero.…”
Section: Discussionmentioning
confidence: 99%
“…The speed at which a population approaches a critical transition is influenced by the rate of change of the system from a steady state. In our case, this is largely governed by the parameter c. As this approach speed could alter the prevalence of early warning signals (Brock and Carpenter 2010;Krkošek and Drake 2014), we simulated 10 time series where the value of c increased linearly (from 1) at different rates (0.025, 0.03, 0.035, . .…”
Section: Detectability Of Early Warning Signals 51mentioning
confidence: 99%
“…These generic leading indicators arise from mathematical properties of stochastic dynamical systems as they approach a tipping point and appear to be present in vastly different systems, including stock markets, global climatic change, and populations (for a review, see Scheffer et al 2009). The development and testing of these statistical early warning signals suggests that a predictive framework for population risk might be developed that requires only a relatively limited amount of demographic data (Hefley et al 2013;Krkošek and Drake 2014). From a conservation perspective, such a framework could provide an important tool for prioritizing conservation efforts and funding to target those species approaching a critical transition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation